Adverse Outcome Pathways Associated with the Ingestion of Titanium Dioxide Nanoparticles - A Systematic Review - Rolo, Dora (2022)
This article belongs to the Special Issue New Insights in Toxicity and Cytotoxicity of Nanomaterials